Impact of COVID 19 Pandemic on TB Control Programme in Nepal: An Overview - Yadav, Rajesh Kumar; Baral, Sushila; Baral, Yadu Nath; Paudel, Srijana (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2021)
COVID19 pandemic is affecting worldwide. TB and COVID-19 both are infectious and primarily affect the lungs and show similar symptoms thus, it is essential to diagnose cases. Accurate diagnostic tests are essential for both TB and COVID-19. COVID 19 has reversed minimum five years of progress in fighting TB. The study is based on review of all available reports, literature, published studies in peer reviewed journal related to COVID-19 pandemic impact on TB control program in Nepal. PubMed, Google scholar, HINARI are the major search engines and or databases used for the review.COVID-19 led lockdown had a significant impact on TB services in Nepal. There is decline in the identification of new cases and had impacted on sputum courier, enrolment, diagnosis and follow up. People cantered delivery of TB prevention, diagnosis, treatment and care services should be ensured in tandem with the COVID-19 response. Health authorities should maintain support to essential TB services during emergencies.